The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00125-008-1092-y
|View full text |Cite
|
Sign up to set email alerts
|

CD40 activation in human pancreatic islets and ductal cells

Abstract: Aims/hypothesis CD40 expression on non-haematopoietic cells is linked to inflammation. We previously reported that CD40 is expressed on isolated human and non-human primate islets and its activation results in secretion of IL-8, macrophage inflammatory protein 1-beta (MIP-1β) and monocyte chemoattractant protein-1 (MCP-1) through nuclear factor-κB and extracellularly regulated kinases 1/2 pathways. The objective of this study was to identify the pattern of gene expression, and to study viability and functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
23
0
3
Order By: Relevance
“…Clinical studies have demonstrated that sCD40L plasma levels are increased in obese patients and positively correlate with BMI, waist circumference, fasting glucose, and leukocyte counts and that sCD40L levels decrease after bariatric surgery (58). CD40 ligation on adipocytes results in activation of classical proinflammatory signal transduction pathways, including extracellular signal-related kinase, p38, Jun NH 2 -terminal kinase, mitogen-activated protein kinase, and nuclear factor-kB (NF-kB), which results in the expression of cytokines and chemokines, including TNF, IL-6, and MCP-1, as well as the prothrombotic mediator plasminogen activator inhibitor 1 (57,59,60). These proinflammatory mediators subsequently activate endothelial cells and immune cells, which promote a generalized proinflammatory AT status.…”
Section: Cd40-cd40lmentioning
confidence: 99%
“…Clinical studies have demonstrated that sCD40L plasma levels are increased in obese patients and positively correlate with BMI, waist circumference, fasting glucose, and leukocyte counts and that sCD40L levels decrease after bariatric surgery (58). CD40 ligation on adipocytes results in activation of classical proinflammatory signal transduction pathways, including extracellular signal-related kinase, p38, Jun NH 2 -terminal kinase, mitogen-activated protein kinase, and nuclear factor-kB (NF-kB), which results in the expression of cytokines and chemokines, including TNF, IL-6, and MCP-1, as well as the prothrombotic mediator plasminogen activator inhibitor 1 (57,59,60). These proinflammatory mediators subsequently activate endothelial cells and immune cells, which promote a generalized proinflammatory AT status.…”
Section: Cd40-cd40lmentioning
confidence: 99%
“…Studies showed that CD40 was expressed in human pancreatic islets and ductal cells and it was up-regulated in pancreatic cancer (16)(17)(18). Because CD40 activation is able to reverse immune suppression and drive antitumor T cell responses (17), researchers have tried the agonist CD40 antibody to treat pancreatic carcinoma and suggested that CD40 held potential to be a treatment target similarly to that in the treatment of other cancer types (17).…”
Section: Introductionmentioning
confidence: 99%
“…5 The co-stimulatory molecule CD40 is expressed on both human and mouse pancreatic islet β-cells and pancreatic duct cells, but not on α-cells. 9 The expression of CD40 on pancreatic islet and ductal cells is increased upon exposure to pro-inflammatory cytokines, including TNF-α, IL-1β and interferon (IFN)-γ, all abundantly present in the diabetic pancreas. 8,9 Whereas membrane-bound CD40L is expressed on immune cells that infiltrate the diabetic pancreas, sCD40L is cleaved from the surface of activated platelets by the proteinase ADAM 10.…”
Section: Cd40-cd40l Interactions In the Pathogenesis Of Pancreatic Inmentioning
confidence: 99%
“…10 Although the biological effects of sCD40L-mediated signalling in T2DM remain largely unknown, binding of membrane-bound CD40L to CD40 on β-cells results in the activation of nuclear factor kappa B (NFκB), and subsequently induces the expression of cytokines, including IL-6, IL-8 and chemokines, such as monocyte chemoattractant protein (MCP)-1 and macrophage inflammatory protein (MIP)-1β. 8,9 This further enhances pancreatic inflammation and impairs β-cell insulin release or production. Although in vitro experiments suggested that insulin metabolism is not affected by CD40L signalling, Poggi et al 22 recently demonstrated that obese CD40L −/− mice have preserved insulin sensitivity and low plasma insulin levels compared to obese CD40L +/+ mice.…”
Section: Cd40-cd40l Interactions In the Pathogenesis Of Pancreatic Inmentioning
confidence: 99%
See 1 more Smart Citation